MANAGEMENT OF MULTIDISCIPLINARY COOPERATION IN CHILD OBESITY TREATMENT - Pastucha, Dalibor; Ripplová, Dana; Vávrová, Petra; Hyjánek, Jiří; Chrastina, Jan (Profese Online, 2010)
The aim of the study was to show how important is cooperation between different branches of medicine in treatment of obesity in children and offer one of possible ways how to organise the treatment of obese children. The theoretical part includes information about child obesity, nutrition and appropriate therapy by physical training.
Keywords: obesity; physical activity; weight; childhood; diet; nutrition